DOI: 10.51415/10321/1510
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impact of primary headaches on students at the Durban based campuses of the Durban University of Technology (DUT)

Abstract: Background Headaches affect different proportions of many populations and are experienced by any age, gender or ethnicity group. There is a paucity of data on the prevalence of headaches in South Africa, particularly amongst the university student population. Previous studies have suggested that headaches impact on daily activities as well as family and/or social activities. Studies on the impact of headaches on students are limited. Aim of Study The aim of this research study was to determine the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some participants felt as if they were a burden and liability to those around them, especially to their families. The literature revealed that migraineurs experienced an emotional impact such as hopelessness, irritability, despair, frustration, anger, guilt, feeling like a burden, a lack of control, mood changes, and feeling isolated from others (Banciu & Bouleanu 2018 :28; Basdav et al 2016 :1680; Mannix et al 2016 :6; Palacios-Ceña et al 2017 :9). Women with migraines without aura were reported to have experienced helplessness and frustration because of the unpredictability, invisibility and permanence of their migraines (Banciu & Bouleanu 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some participants felt as if they were a burden and liability to those around them, especially to their families. The literature revealed that migraineurs experienced an emotional impact such as hopelessness, irritability, despair, frustration, anger, guilt, feeling like a burden, a lack of control, mood changes, and feeling isolated from others (Banciu & Bouleanu 2018 :28; Basdav et al 2016 :1680; Mannix et al 2016 :6; Palacios-Ceña et al 2017 :9). Women with migraines without aura were reported to have experienced helplessness and frustration because of the unpredictability, invisibility and permanence of their migraines (Banciu & Bouleanu 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, friends, family or colleagues assisted migraineurs when they could not perform tasks (Gibbs et al 2020 :1351; Peters et al 2005 :44). The local literature revealed that among South African university students who attended social events (60% of the population were women), migraineurs left early, drank water, requested medication or isolated themselves (Basdav 2016 :3). There were only two participants who did not experience a history of strained relationships in this study and most of the participants have since built more supportive relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation